Intraoperative Blood Loss in Female Patients with Adolescent Idiopathic Scoliosis during Different Phases of the Menstrual Cycle - Li, Chao (PLoS One, 2014)
BACKGROUND: The vast majority of AIS patients who require surgical intervention are women. Blood loss is a major concern during the operation. METHODS: The medical records of all female AIS patients who underwent posterior correction and fusion operations using the all-pedicle screw system from January 2012 to January 2014 were reviewed. Patients with irregular menstruation; underwent osteotomy; use coagulants were excluded from the study. The remaining patients were divided into 4 groups according to the operation date in the menstrual cycle (A: premenstrual group, 24–30 d; B: follicle group, 6–11 d; C: ovulatory group, 12–17 d; D: luteal group, 18–23 d). The information of patients from the 4 groups was reviewed. The data was analyzed using analysis of variance, the Student-Newman-Keels test and Kruskal-Wallis Test. RESULTS: A total of 161 patients were included in this study. There were 40 patients included in group A, 38 patients in group B, 41 patients in group C and 42 patients in group D. The 4 groups were matched in age (P = 0.238), body height (P = 0.291), body weight (P = 0.756), Risser sign (P = 0.576), mean curve Cobb angle (P = 0.520), and bending flexibility index (P = 0.547), the number of levels fused (P = 0.397). The activated partial thromboplastin time (P = 0.235) and prothrombin time (P = 0.074) tended to be higher in group A, but the difference was not statistically significant. The fibrinogen level was lower in group B than the other 3 groups (P = 0.039). Blood loss and normalized intraoperative blood loss (NBL) was significantly higher in group A than the other 3 groups (P<0.01). CONCLUSIONS: The hemostatic function tended to be lower in the premenstrual phase. The fibrinogen level was lowest in the mid-follicle phase. Female AIS patients tended to endure more intraoperative blood loss when the operation was performed in the premenstrual phase during the menstrual cycle.